USE INTERACTIVE TECHNIQUES IN ELEMENTARY SCHOOL MATHEMATICS CLASSES - M.Musurmonova,E.Sherdanova,A.Yusupova (Ethiopian International Journal of Multidisciplinary Research, 2025)
The article talks about the importance of the use of interactive methods in elementary school mathematics lessons in improving the effectiveness of the lesson and in the formation of sharpness and mathematical thinking of students.